Electrospinning‐on‐Electrode Assembly for Air‐Cathodes in Microbial Fuel Cells. Issue 24 (20th November 2018) - Quaglio, Marzia; Chiodoni, Angelica; Massaglia, Giulia; Delmondo, Luisa; Sacco, Adriano; Garino, Nadia; Castellino, Micaela; Bianco, Stefano; Margaria, Valentina; Salvador, Gian Paolo; Pirri, Candido Fabrizio
Abstract: A binder‐free electrospinning‐on‐electrode (EoE) assembly is proposed for the decoration of nonflat electrodes with nanostructured catalysts. EoE assembly exploits the modulation of the electric field induced by conducting protrusions. Using nonflat electrodes as collectors, EoE assembly allows the arrangement of nanostructured catalyst with optimized electrochemical interfaces. This work discusses the decoration of carbon paper electrodes with nanostructured manganese oxide to catalyze the oxygen reduction reaction (ORR). Carbon fibers on top of carbon paper act as conductive protrusions, locally enhancing the electric field, and thus inducing a preferential arrangement of the electrospun. Two nanostructured Mn3 O4 are obtained by EoE assembly, i.e., nanofibers and nanobeads. The catalytic behavior toward ORR is evaluated by rotating ring disk electrode analysis. The EoE‐based cathodes with the catalyst shaped as nanofibers have exchanged 3.81 electrons during ORR, while nanobeads have reached 3.9 electrons, behaving similarly to standard Pt/C‐based electrodes. Electrodes are then tested in single chamber microbial fuel cell with air breathing cathode. Devices having cathodes decorated with Mn3 O4 nanobeads achieve a power output comparable to that obtained by Pt‐based cathodes. The impressive result can be attributed to the good quality of the electrochemical interfaces formed by the electrospinning‐based processing as demonstrated by electrochemical impedance spectroscopy. Abstract : The electrospinning‐on‐electrode assembly is proposed as a fast and facile method to directly deposit nanostructured catalyst on the electrode. Nanostructured Mn3 O4 is deposited on carbon conductive electrodes exposing structured surfaces: the resulting electrodes show outstanding performances toward the oxygen reduction reaction. Used as cathodes in microbial fuel cells they demonstrate a behavior close to that of the reference Pt/C‐based electrode.